Fusão Homotípica e Heterotípica entre Vacúolos Parasitóforos de Leishmania spp - Real, Fernando [UNIFESP] (2011)
Most non-viral intracellular pathogens gain entrance into human and animal host cells by “classic” or modifIed phagocytosis and are thus lodged in phagosomes which they may or not continue to occupy in the course of infection. Their survival and multiplication within host cells depend on modulation of the compositional and functional phenotypes of the phagosomes they occupy, including intravacuolar pH, substrate acquisition through membrane transporters and channels, and fusion with lysosomes, and other cell phagosomes and vesicles. Each phagosome thus exhibits particular features, whose biogenesis is conditioned to different signals triggered by both the host cell and the internalized particle/microorganism. Once internalized by host cells, some pathogens escape the phagosome and assume the host cell cytosol as their intracellular niche. Other pathogens interfere with phagosomal maturation, leading to the development of phagosomes excluded from host cell endocytic and secretory pathways or vacuoles with selective fusogenic properties. During their intracelular lifecycle, protozoan parasites of the genus Leishmania remain enclosed in phagolysosome-like structures called Parasitophorous Vacuoles (PVs). The morphological and biochemical diversity of Leishmania PVs were not extensively studied. Most species – such as L. major, L. donovani and L. braziliensis – are lodged in membrane-bound PVs, containing one or two amastigotes, that undergo fission as parasites divide. The mechanisms involved in PV fission remain to be elucidated. In contrast, species from the L. mexicana complex, such as L. amazonensis, L. mexicana and L. pifanoi, occupy large PVs which may contain many parasites. The present experimental aimed to answer the question: “what is the importance of a speciesspecific PV to Leishmania intracellular parasitism?”. In the experiments herewith described, mouse bone marrow-derived macrophages were co-infected with two Leishmania species to investigate the possibility of fusion between PVs that shelter different parasites, and the consequences of a possible intravacuolar cohabitation on their survival and multiplication. Macrophages were initially infected with L. amazonensis and later on superinfected with L. major, which represent species with different PV size, parasite content and biogenesis. In order to distinguish the two species, macrophages were infected with non-fluorescent L. amazonensis amastigotes and superinfected with either amastigotes or promastigotes of L. major transfected with the fluorescent proteins GFP or DsRed2. Although PVs contacted each other, fusion between L. amazonensis and L. major amastigote PVs was not detected. Leishmania major multiplication and PV fission were not affected by coinfection. In contrast, PVs containing L. major promastigotes fused with pre-established L. amazonensis PVs. In these “chimeric” vacuoles (containing both Leishmania), L. major promastigotes multiplied, however they did not differentiate into amastigotes. The differentiation of L. major promastigotes into amastigotes occurred exclusively within their own, unfused PVs.